Rancang Bangun Aplikasi Resep Makanan Berbasis Android Menggunakan Framework Flutter - Riska Anand; Ummul Khair; Yuyun Dwi Lestari (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Humans as living beings cannot be separated from the need for food. One of the activities in making food iscooking. People in general view food recipes in books or magazines where this method is considered inconvenientfor some people. This research was conducted to design an android-based recipe application, which will providesolutions to the community to make it easier to get food recipe information. This application provides food recipesfrom several well-known chefs in Indonesia such as Renatta Moeloek, Junior John Rorimpandey, ArnoldPoernomo and Farah Fauzan Quinn. This application is designed using the Flutter Framework and the Dartprogramming language through the Visual Studio Code editor. Previous research was carried out by HandikaJuliansyah, 2020 in creating an android-based Al-Qur'an application that aims to implement the FlutterFramework as a tool to build an Android-based Al-Qur'an application. Flutter itself is an SDK made by Googlewhich is intended for high-performance mobile apps development. Mobile apps developed with Flutter can bepublished to both Android and iOS platforms from a single codebase. Based on the test results, this Android-basedrecipe application successfully runs on the Android operating system version 7.0 (Nougat).